2021
DOI: 10.24136/oc.2021.011
|View full text |Cite
|
Sign up to set email alerts
|

The nonlinear relationship between financial flexibility and enterprise risk-taking during the COVID-19 pandemic in Taiwan?s semiconductor industry

Abstract: Research background: Risk-taking is the basis for sustainable development of enterprise. It was clear that the influence COVID-19 epidemic on the global market economy has increased operational risks for businesses. The semiconductor industry has high operating risks and financial risks. Moderate financial flexibility (FF) can improve the ability of semiconductor enterprises to acquire financial resources in real time, calmly cope with the impact of uncertainties in operation, improve investment opportunities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 50 publications
1
13
1
1
Order By: Relevance
“…Control variables: The control variables are company size (SIZE), financial leverage (LEV), firm age (AGE), net profit margin (NPM), and growth rate of owner's equity (OEG), as previous studies found they determined SGR (or ROE) [39,[61][62][63]. SIZE is measured by the natural logarithm of total assets; LEV = total liabilities/shareholder's equity; AGE stands for firm age; NPM refers as the ratio of net income to sales; and OEG = (owner's equity of current period-owner's equity of previous period)/owner's equity of previous period.…”
Section: Variablesmentioning
confidence: 99%
“…Control variables: The control variables are company size (SIZE), financial leverage (LEV), firm age (AGE), net profit margin (NPM), and growth rate of owner's equity (OEG), as previous studies found they determined SGR (or ROE) [39,[61][62][63]. SIZE is measured by the natural logarithm of total assets; LEV = total liabilities/shareholder's equity; AGE stands for firm age; NPM refers as the ratio of net income to sales; and OEG = (owner's equity of current period-owner's equity of previous period)/owner's equity of previous period.…”
Section: Variablesmentioning
confidence: 99%
“…As a result, the corporation can dominate with a larger selection of high-quality products thanks to an optimized supply chain. Additionally, these aspects will benefit its subsequent exports and consumer relationships [2].…”
Section: Results Of the Questionnaire Survey And Identification Of Tr...mentioning
confidence: 99%
“…In comparison to the rest of the world, the legislative environment is now weak and even chaotic in some regions. Only when businesses have the resources to conduct their own research and development will Slovakia experience exponential growth in terms of added value [2].…”
Section: Results Of the Questionnaire Survey And Identification Of Tr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Temporary outages in production, services and trade resulted in increased unemployment (Svabova et al, 2021). Operational risk for companies has also increased during this period (Chang and Wu, 2021). Global stock markets have also reacted to news of the spread of the virus.…”
Section: Introductionmentioning
confidence: 99%